CREATIVE METHODS FOR DEVELOPING LISTENING COMPREHENSION SKILLS IN ENGLISH (SCIENCE TIME JOURNAL, 2026)
This scientific article highlights the most effective and modern methods for developing listening skills for learners of English as a foreign language. Listening comprehension is considered one of the most critical parts of the foreign language learning process. Listening to understand is not just about receiving information, but also about analyzing and understanding the content of the received information. This article analyzes the problems associated with the listening comprehension process and creative ways to overcome them. During the analysis, the shadowing technique, audio-visual materials, and several similar methods are studied, and the extent to which they develop students' listening comprehension is determined. At the end of the article, practical recommendations are provided for bot teachers and independent learners of foreign languages.